THE ROLES OF MACROBENTHIC MOLLUSCS STRUCTURE IN ASSESSING ECOLOGICAL STATUS AT MANGROVE AND AQUACULTURE AREAS (Jurnal Teknologi (Sciences & Engineering), 2023)
stability of Coastal water ecosystem could have an effect on mangrove vegetation and anthrophogenic activities. This stability correlates significantly with the structure of the macrobenthic mollusk community in the area, some of this biota are bioindicator agents. This study aims to assess the ecological functions of macrobenthic molluscs, evaluate the spatial and temporal differences in their community structure, and analyze their correlation to environmental parameters in aquaculture and mangrove areas in the Karimunjawa Islands, Jepara, Central Java, Indonesia. Purposive random sampling method was conducted at KJABB-IMTA aquaculture and mangrove areas between July and September 2021. Collected data were analyzed using k-dominance curve, NMDS ordination, PCA, and BIO-ENV using Primer 6.1.5 software. Based on Paired T Test result, comparison between each location showed significant difference (t=15.916, P<0.05, dF=5) meanwhile comparison between each sampling period showed insignificant result. The highest abundance and diversity were found in the aquaculture area and dominated by gastropods. Significant differences occurred in the structure of macrobenthic molluscs between the two study locations (t=15.916, P<0.05, df=5), while the comparison between their composition and abundance between sampling times was not significant. The abiotic elements that primarily impact the structure of macrobenthic mollusks are the particle size composition of the substrate (mud) and dissolved oxygen (DO) based on PCA and BIO-ENV analysis (BIO-ENV; r=0.733).